Chronic mycobacterial meningitis due to Mycobacterium chelonae: a case report - Shokrallah Salmanzadeh (International Journal of Infectious Diseases, 2014)
We report a case of chronic meningitis due to Mycobacterium chelonae. This organism is a rapidly growing Mycobacterium (RGM) and can be found worldwide in environmental sources such as soil, dust, and water. M. chelonae is an uncommon cause of meningitis; the majority of infections caused by this organism are localized cutaneous or soft tissue infections, and rarely lung infections. The organism is indistinguishable phenotypically, so we applied PCR based on the rpoB gene sequence followed by restriction fragment length polymorphism (RFLP) for molecular identification. The subsequent sequencing of RFLP products revealed 99.7% similarity with M. chelonae.